OPTIMIZATION ALGORITHM FOR INTOGRETING DISTRIBUTED GENERATORS IN RADIAL DISTRIBUTION NETWORK (Academia Science Repository, 2023)
This paper introduces a hybrid approach to find the optimal location and size of distributed generations (DG) in the radial distribution network (RDN). The proposed approach is based on the whale optimization algorithm (WOA) technique to calculate the optimal allocation of DGs and loss sensitivity index (LSI) to obtain the best buses for DGs installation in RDN.